2015
DOI: 10.1007/s00198-015-3427-0
|View full text |Cite
|
Sign up to set email alerts
|

Regional and seasonal variations in ultraviolet B irradiation and vitamin D synthesis in India

Abstract: The mean UVBI was highest between 11 am and 1 pm throughout the year in all locations. No increase in the serum 25(OH)D levels was observed following sun exposure in winter, emphasizing the need for vitamin D supplementation during these months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…[5] A similar association is proven across India in adolescent school children aged 10–15 years by Marwaha et al [6]…”
mentioning
confidence: 53%
“…[5] A similar association is proven across India in adolescent school children aged 10–15 years by Marwaha et al [6]…”
mentioning
confidence: 53%
“…Regression models predicted that a mere 30 min/week sunshine exposure between 10.00 am and 2.00 pm to prone infants clothed in diapers would result in normal vitamin D level at six months of age. However, in another before-after evaluation in 10-to 15-year-old healthy school children, no increase in serum 25(OH)D level was documented [11]. These findings may be reflective of suboptimal sunlight exposure in winter months (30 minutes/d on 10% body surface area for 4 weeks).…”
Section: Vitamin D Sufficiency Through Sunshine Inmentioning
confidence: 85%
“…Just after it reaches a plateau, the cutaneous vitamin production is again hampered by the monsoon season and the following winter season, thus rendering our participants vitamin D-deficient for many months of the year. Marwaha et al (27) found a significant decrease in mean 25(OH)D levels during winter despite sun exposure. Second, a very important role is that of degradation of precholecalciferol into suprasterol I and II on prolonged exposure to sunlight (28) .…”
Section: Average Daily Vitamin D Synthesis In Rural Womenmentioning
confidence: 97%